Towards a model evaluation protocol for urban scale flow and dispersion models. (1st January 2011) - Di Sabatino, S.; Olesen, H.R.; Berkowicz, R.; Franke, J.; Schatzmann, M.; Leitl, B.; Schlünzen, K. Heinke; Britter, R.; Martilli, A.; Carissimo, B.
This paper reports on the stages forming a model evaluation protocol for urban flow and dispersion models proposed within the COST Action 732 on "Quality Assurance and Improvement of Micro-Scale Meteorological Models". It discusses the different components forming model evaluation with emphasis on validation and implementation of the protocol for the test case Mock Urban Setting Test (MUST). The protocol was proposed with building-resolving models in mind, but integral models have also been included. The suggested approach can be used for further micro-scale model evaluation and for the standardisation of their applications.